1997
DOI: 10.1044/jslhr.4003.627
|View full text |Cite
|
Sign up to set email alerts
|

Disfluency in Spasmodic Dysphonia

Abstract: This study examined visual analog scaling (VAS) judgments of disfluency by normal listeners in response to oral reading by speakers with spasmodic dysphonia (SD) and by nondysphonic controls, as well as the variables of frequency of occurrence of disfluencies, speaking rate, number of reading errors, and temporal acoustic measures of interword interval duration and articulation time. MANOVA yielded statistically significant differences between SD and control speakers for all variables except reading errors. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…All of these dimensions have been used to describe ADSD speech in the literature (Cannito et al, 1997(Cannito et al, , 2012Zwirner et al, 1993). They also described speech characteristics that extended beyond voice quality; for example, participants noted ''misarticulations,'' choppiness and a halting manner consistent with the reduced intelligibility and voice breaks often associated with ADSD (Cannito et al, 1997). Listeners seemed to draw strong connections between the degree of vocal effort in a sample and its overall severity (Eadie et al, 2007;Zwirner et al, 1993).…”
Section: Perceptual Features Of Adsdmentioning
confidence: 96%
See 1 more Smart Citation
“…All of these dimensions have been used to describe ADSD speech in the literature (Cannito et al, 1997(Cannito et al, , 2012Zwirner et al, 1993). They also described speech characteristics that extended beyond voice quality; for example, participants noted ''misarticulations,'' choppiness and a halting manner consistent with the reduced intelligibility and voice breaks often associated with ADSD (Cannito et al, 1997). Listeners seemed to draw strong connections between the degree of vocal effort in a sample and its overall severity (Eadie et al, 2007;Zwirner et al, 1993).…”
Section: Perceptual Features Of Adsdmentioning
confidence: 96%
“…For example, most participants mentioned the strained, hoarse, harsh, effortful voice quality of the samples. All of these dimensions have been used to describe ADSD speech in the literature (Cannito et al, 1997(Cannito et al, , 2012Zwirner et al, 1993). They also described speech characteristics that extended beyond voice quality; for example, participants noted ''misarticulations,'' choppiness and a halting manner consistent with the reduced intelligibility and voice breaks often associated with ADSD (Cannito et al, 1997).…”
Section: Perceptual Features Of Adsdmentioning
confidence: 98%
“…ADSD severity ratings were established by consensus of two speech pathologists familiar with the disorder and have been shown to be reliable in previous research. 4,25 This yielded equal sample sizes in the mild-to-moderate and severe-toprofound ranges. In addition, all selected speech samples were required to exhibit the full set of vowel tokens targeted for acoustical analysis.…”
Section: Participantsmentioning
confidence: 97%
“…However, by comparing the speaking rate of normal and SD speakers, the authors of [2] found out that speech disfluency (≈ stuttering) is "not a defining feature of SD", although "it does contribute significantly to the overall clinical impression of severity of the disorder. "…”
Section: Which Speech Characteristics Should We Usementioning
confidence: 99%